Pelatihan Teknologi PHT Cabai Merah pada Kelompok Tani Zanonewuku di Kota Tomohon - Baideng, Eva Lienneke; Paat, Frangky J.; Rumende, Roiije R.H.; Butarbutar, Regina R. (Penerbit Widina, Widina Media Utama, 2024)
The Zanonewuku farmer group is in Matani Dua Village, which is one of the horticultural centers in Tomohon City. Commodities grown by this farmer group include red chilies (Capsicum annum). The use of chemicals in agricultural activities is still a mainstay for farmers in maximizing agricultural yields. Chemical pesticide spraying is carried out routinely 2 to 3 times every week. Unwise use of chemical pesticides can damage the environment and the final product produced contains excessive chemical residues. The aim of this community service activity is to provide outreach and training regarding integrated pest management (IPM) in chili cultivation. Socialization in the form of education about integrated pest and disease control techniques (IPM) for chili plants using biological materials and the impact of excessive use of chemical pesticides if used in the long term. The training carried out included making soursop leaf extract vegetable pesticides and making trichoderma which is a biological fertilizer and biofungicide. From this activity, farmers gain increased knowledge and skills about alternative uses of natural ingredients in making pesticides and trichoderma.ABSTRAKKelompok tani Zanonewuku berada di Kelurahan Matani Dua, yang merupakan salah satu sentra hortikultura di Kota Tomohon. Komoditas yang ditanam pada kelompok tani ini termasuk cabai merah (Capsicum annum). Penggunaan bahan kimia dalam kegiatan pertanian masih menjadi andalan petani dalam memaksimalkan hasil pertanian. Penyemprotan pestisida kimia dilakukan secara rutin sebanyak 2 hingga 3 kali setiap minggu. Penggunaan pestisida kimia yang kurang bijak dapat merusak lingkungan dan produk akhir yang dihasilkan mengandung residu kimia yang berlebihan. Tujuan kegiatan pengabdian kepada masyarakat ini adalah memberikan sosialisasi dan pelatihan terkait pengendalian hama secara terpadu (PHT) pada budi daya cabai. Sosialisasi berupa penyuluhan tentang teknik pengendalian hama penyakit secara terpadu (PHT) tanaman cabai menggunakan bahan hayati dan dampak penggunaan pestisida kimia secara berlebihan jika digunakan dalam jangka panjang. Pelatihan yang dilakukan meliputi pembuatan pestisida nabati ekstrak daun sirsak dan pembuatan trichoderma yang merupakan pupuk hayati dan biofungisida. Dari kegiatan ini petani mendapatkan peningkatan pengetahuan dan ketrampilan tentang alternatif pemakaian bahan alami dalam membuat pestisida maupun trichoderma.